2019
DOI: 10.1016/j.jfda.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of drug-metabolizing enzymes and membrane transporters by inflammation: Evidences in inflammatory diseases and age-related disorders

Abstract: Drug-metabolizing enzymes (DMEs) and membrane transporters play important roles in the absorption, distribution, metabolism, and excretion processes that determine the pharmacokinetics of drugs. Inflammation has been shown to regulate the expression and function of these drug-processing proteins. Given that inflammation is a common feature of many diseases, in this review, the general mechanisms for inflammation-mediated regulation of DMEs and transporters are described. Also, evidences regarding the aberrant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 108 publications
1
57
0
Order By: Relevance
“…Similar downregulation of DMETs in preclinical models of certain chronic inflammatory diseases has been recently reviewed ( Wu & Lin, 2019 ). Various models of colitis ( Chaluvadi, Kinloch, et al, 2009 ; Masubuchi et al, 2008 ) and arthritis ( Ashino et al, 2007 ; Dickmann et al, 2012 ; Sanada et al, 2011 ) show diminished hepatic expression and/or activity of many CYP450 enzymes (CYP3A, 4A, 2C, 1A2, and 2E1).…”
Section: Regulation Of Dmets By Inflammationmentioning
confidence: 63%
See 2 more Smart Citations
“…Similar downregulation of DMETs in preclinical models of certain chronic inflammatory diseases has been recently reviewed ( Wu & Lin, 2019 ). Various models of colitis ( Chaluvadi, Kinloch, et al, 2009 ; Masubuchi et al, 2008 ) and arthritis ( Ashino et al, 2007 ; Dickmann et al, 2012 ; Sanada et al, 2011 ) show diminished hepatic expression and/or activity of many CYP450 enzymes (CYP3A, 4A, 2C, 1A2, and 2E1).…”
Section: Regulation Of Dmets By Inflammationmentioning
confidence: 63%
“… a List of publications indicated in this table is not exhaustive. For example, because studies investigating the impact of diabetes on various animal models were recently reviewed ( Wu & Lin, 2019 ) , this table does not include the works discussed in that review, except those which were published after its publication. b According to Yao et al (2019) , human CYP2C9 and CYP2C19 corresponds to CYP2C11 and CYP2C22 in rats.…”
Section: Regulation Of Dmets By Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 In the present study, there were no significant differences between the elderly and adult cohorts in terms of sex, infection site, liver function and the distribution of CYP2C19 genotype, and the major route of administration in both cohorts was intravenous. Human ageing has been described as a chronic and low-grade inflammatory condition, and ageing is considered as a regulatory factor in drug metabolism/transport, 26 which might partially explain the lack of association between the voriconazole-related concentrations and the CYP2C19 * 2 or CYP2C19 * 3 polymorphism in elderly patients. A previous study reported reduced CYP2C19 and CYP2C9 levels in the ageing human population and suggested that the metabolic activity of CYP2C19 is age-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have posited that disease states, as well as sex-and age-related differences can alter the expression of drug metabolizing enzymes (DMEs), and in turn change the metabolism and detoxification of drugs by remodeling the hepatic absorption, distribution, metabolism and excretion (ADME) (Court, 2010;Nyagode et al, 2014;Xu et al, 2019;Wu & Lin, 2018). Therefore, we specifically investigated the changes in DME expression levels in a disease model with age-and sex-related differences.…”
Section: Introductionmentioning
confidence: 99%